Global Networks of Innovation - Bueno Castellanos, Carmen (Revista de Antropología Social, 2012)
This essay aims to analyze global processes in the local. For this purpose, it presents the ethnography of one of the icons of globalization: De-territorialized production networks. In particular, complex and multiple processes through which global firms generate innovations. It analyzes the leeway the subsidiaries of this firms localized in Mexico have, to bring out collaborations at the local level geared toward the production of new knowledge and trigger innovation environments. Also it points out, national small enterprise’s resources and linkages to participate in these global networks and contribute with products that incorporate innovations.
Keywords: Innovation; global firms; local enterprises; regional development